2016
DOI: 10.1002/2016ja022337
|View full text |Cite
|
Sign up to set email alerts
|

A linear scale height Chapman model supported by GNSS occultation measurements

Abstract: Global Navigation Satellite Systems (GNSS) radio occultations allow the vertical sounding of the Earth's atmosphere, in particular, the ionosphere. The physical observables estimated with this technique permit to test theoretical models of the electron density such as, for example, the Chapman and the Vary‐Chap models. The former is characterized by a constant scale height, whereas the latter considers a more general function of the scale height with respect to height. We propose to investigate the feasibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 24 publications
5
37
0
Order By: Relevance
“…Also, our results are supported by the need in increase of the electron density scale height above F2‐layer peak recently confirmed with direct radio occultation GPS measurements (Hernández‐Pajares et al, ; Olivares‐Pulido et al, ).…”
Section: Resultssupporting
confidence: 88%
“…Also, our results are supported by the need in increase of the electron density scale height above F2‐layer peak recently confirmed with direct radio occultation GPS measurements (Hernández‐Pajares et al, ; Olivares‐Pulido et al, ).…”
Section: Resultssupporting
confidence: 88%
“…These results are well maintained when the maximum available SLTA value, h 2 , is increased: just a slight overall improvement (reduction of relative error of about 2%) is obtained for h 2 =550 km, compared with the EPS‐SG case of h 2 =500 km studied in this work. This last result is compatible with the accurate description given by the Vary‐Chapman model under the assumption of scale height linearly dependent with the altitude at the topside part of the EDP, as detailed in Olivares‐Pulido et al [].…”
Section: Computations and Resultssupporting
confidence: 88%
“…Some interesting features can be verified in the estimated spatial distributions of H 0 , which were obtained with similar magnitude as in previous works (Liu et al, ; Olivares‐Pulido et al, ) and with similar magnitude of H s derived from the neutral temperature of IRI ( H IRI ). A similar consistency of H 0 and H 1 was obtained, with small differences due to the contribution of ∂ H 0 /∂ h .…”
Section: Spatial Modelingsupporting
confidence: 87%
“…Olivares‐Pulido et al () have found that linear functions can be used to well estimate the variability of the scale height at the topside when adjusted to RO data, finding the Pearson coefficient above 0.98 for more than 72% of the analyzed RO ionospheric profiles. In this regard, the varying scale height is approximated as the following linear equation: Hs(h)=H0∂h(hhm)+H0 where H 0 stands for the scale height referred to the peak height and ∂ H 0 /∂ h to the gradient of H 0 .…”
Section: New Procedures To Estimate the Vary‐chap Functionmentioning
confidence: 99%
See 1 more Smart Citation